Feasibility of supported self-management with a pictorial action plan to improve asthma control - Shariff Ghazali, Sazlina; Lee, Ping Yein; Cheong, Ai Theng; Hussein, Norita; Pinnock, Hilary; Salim, Hani; Liew, Su May; Hanafi, Nik Sherina; Abu Bakar, Ahmad Ihsan; Ng, Chiu Wan; Ramli, Rizawati; Mohd Ahad, Azainorsuzila; et al. (Nature Publishing, 2022)
Supported self-management reduces asthma-related morbidity and mortality. This paper is on a feasibility study, and observing the change in clinical and cost outcomes of pictorial action plan use is part of assessing feasibility as it will help us decide on outcome measures for a fully powered RCT. We conducted a pre-post feasibility study among adults with physician-diagnosed asthma on inhaled corticosteroids at a public primary-care clinic in Malaysia. We adapted an existing pictorial asthma action plan. The primary outcome was asthma control, assessed at 1, 3 and 6 months. Secondary outcomes included reliever use, controller medication adherence, asthma exacerbations, emergency visits, hospitalisations, days lost from work/daily activities and action plan use. We estimated potential cost savings on asthma-related care following plan use. About 84% (n = 59/70) completed the 6-months follow-up. The proportion achieving good asthma control increased from 18 (30.4%) at baseline to 38 (64.4%) at 6-month follow-up. The proportion of at least one acute exacerbation (3 months: % difference -19.7; 95% CI -34.7 to -3.1; 6 months: % difference -20.3; 95% CI -5.8 to -3.2), one or more emergency visit (1 month: % difference -28.6; 95% CI -41.2 to -15.5; 3 months: % difference -18.0; 95% CI -32.2 to -3.0; 6 months: % difference -20.3; 95% CI -34.9 to -4.6), and one or more asthma admission (1 month: % difference -14.3; 95% CI -25.2 to -5.3; 6 months: % difference -11.9; 95% CI -23.2 to -1.8) improved over time. Estimated savings for the 59 patients at 6-months follow-up and for each patient over the 6 months were RM 15,866.22 (USD3755.36) and RM268.92 (USD63.65), respectively. Supported self-management with a pictorial asthma action plan was associated with an improvement in asthma control and potential cost savings in Malaysian primary-care patients.